Causes and impacts of farmer-herder conflicts through a political economy and food production lens: Case study in Gadarif State, Sudan - Sulieman, Hussein (CGIAR System Organization, 2024)
Farmer-herder conflicts have become a significant challenge in Gadarif State, Sudan, threatening livelihoods and food security. This report examines the causes and impacts of FHCs through a political economy and food production lens, focusing on the interaction between the farming community of Azaza Sogora Village and the Fallata pastoralist group.